Quality of Life, Peer Social Support, and Mental Health among Students with Disabilities in Indonesia - Agung Daniel Fhilipino Kase Lie; Arthur Huwae (Kuras Institute, 2025)
Although research on student Mental Health has been widely conducted, there is still a gap in studies that specifically examine the relationship between Quality of Life and Peer Social Support on the Mental Health of students with disabilities in the context of higher education in Indonesia. Students with disabilities in higher education often face significant psychological challenges, such as accessibility barriers, social stigma, and academic pressure that can affect their Mental Health. This study aims to investigate the role of Quality of Life and Peer Social Support in influencing the Mental Health of students with disabilities in Indonesia. The research method uses a quantitative approach with multiple linear regression analysis. The research sample consisted of 104 students with disabilities aged 19-23 years, obtained using accidental sampling techniques. The research instruments consist of the Indonesian Quality of Life Scale (α = 0.942), the Peer Support Questionnaire (α = 0.858), and the Azira Mental Health Scales (α = 0.929). The research results indicate that Quality of Life and Peer Social Support together are a significant predictor of Mental Health (F = 78.163; p = 0.000). Partially, Quality of Life is a significant predictor of Mental Health (t = -12.503; p = 0.000), whereas Peer Social Support does not show a significant predictor of Mental Health (t = -0.030; p = 0.976). These findings emphasize the importance of improving the Quality of Life for students with disabilities as a key strategy in Mental Health interventions, while Peer Social Support needs to be optimized to be more effective in providing a positive impact.